Music in the public schools - Jones, Thomas Lormar (My University, 1896)
Introduction: Music is everywhere; in the forest where the little birds sing and cheer up the lonely traveler who passes by; even the babbling of the brook, the sighing of the breeze, produce sounds which are pleasing to the ear. What a world this would be without music. How lonely, how burdensome would be the task if there was nothing to break the monotony of the working man.
Citation: Jones, Thomas Lormar. Music in the public schools. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Music; Birds; Monotony; Working man; Theses; Manuscripts (documents)